The effect of blended learning in improving transitional speed and teaching the skill of dribbling in soccer for second grade students (Journal of the College of Basic Education, 2023)
Summary of the research:The objective of the current research is to study the impact of blended learning in improving the transitional speed and teaching the skill of dribbling in football for the second intermediate grade students, through the preparation of an educational program and it was presented to experts, and the principles that are compatible with the lesson of physical education were selected, especially in the game of football. In the second chapter, it included theoretical studies, and the third chapter included field research procedures, as the research community was chosen by the intentional method from the students of the Baghdad Education Schools, Al-Rusafa, the third - Al-Amanaa Intermediate School for Boys - the second grade average, as the total research community reached (179) students, distributed among (4 As for the research sample, the researcher drew lots to select (20) students from them randomly, and after arranging them in ascending order, they were divided into two groups (experimental and control), with (10) students from Division (A) as an experimental group and (10) Students from Hall (B) as a control group applied the educational program to the experimental research sample, and it lasted for eight weeks, with two educational units per week. Thus, the total educational units reached (16) educational units, and then the researchers conducted post-tests for the experimental and control groups, and in the fourth chapter, the results were processed statistically Between the pre and post tests for each experimental and control group separately, and the results were processed statistically between the post tests for the experimental and control groups, and it was found from the results of the tests that there were significant differences between the results of the pre and post tests for the control and experimental groups, and the emergence of significant differences between the results of the post tests for the experimental and control groups, in favor of the results of the post tests. The results of the study were presented and discussed, and in the fifth chapter, the conclusions reached by the two researchers were presented, with the emergence of an effective effect of the effect of blended learning in improving transitional speed and teaching the skill of dribbling in football for second-grade students. It was recommended to conduct similar studies with different games and different age groups.